A New Fossil Perca Fish (Teleostei, Percidae) from the Neopleistocenian Sediments of Southern Ukraine - Kovalchuk, О.М. (Вестник зоологии, 2013)
A new fossil species Perca neopleistocenica Kovalchuk, sp. n. from Southern Ukraine is described. It differs from other species of the genus by width and configuration of praeoperculum, and also by quantity of cogs on the posterior edge of os praeoperculare.